2005
DOI: 10.1038/sj.onc.1208740
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine receptor 7 activates phosphoinositide-3 kinase-mediated invasive and prosurvival pathways in head and neck cancer cells independent of EGFR

Abstract: Chemokine receptor 7 (CCR7) upregulation, which mediates immune cell survival and migration to lymph nodes, has recently been associated with nodal metastasis of squamous cell carcinoma of the head and neck (SCCHN). However, the mechanism of CCR7 in tumor progression, its downstream signaling mediators, and interactions with other pathways contributing to metastasis of SCCHN have not been determined. We hypothesized that inflammatory chemokine-mediated signals could also promote tumor proliferation and mitogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(75 citation statements)
references
References 29 publications
3
71
1
Order By: Relevance
“…Wang et al (2004) reported upregulation of CCR7 expression in metastatic tumour lines from 14 patients with SSCHN. Furthermore, Wang et al (2005) have shown that CCR7-triggered signalling through the phosphoinositide-3-kinase (PI-3K/protein kinase B (PKB/AKT) signalling cascade is directly involved in chemotaxis and tumour cell invasion of matrigel in vitro in two SCCHN cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al (2004) reported upregulation of CCR7 expression in metastatic tumour lines from 14 patients with SSCHN. Furthermore, Wang et al (2005) have shown that CCR7-triggered signalling through the phosphoinositide-3-kinase (PI-3K/protein kinase B (PKB/AKT) signalling cascade is directly involved in chemotaxis and tumour cell invasion of matrigel in vitro in two SCCHN cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…The results are representative of three independent experiments. Expression relative to β-actin is shown as the mean ± Sd ( ccR7 has been shown to interact with chemokines (ccL19, ccL21) and modulate migration, invasion and proliferation of metastatic SccHN (10,11,28). However, the mechanisms and the signaling pathways underlying ccR7-mediated adhesion and migration remain poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…PcI-37B cells were cultured as previously described (10,11,28) in Dulbecco's modified eagle's medium (DMeM) (Invitrogen, carlsbad, cA, USA), supplemented with 10% fetal bovine serum (FBS) (gibco, carlsbad, cA, USA), 100 U/ml penicillin g, and 100 U/ml streptomycin in an atmosphere of 95% air/5% cO 2 at 37˚C. When inhibitors were used, inhibitor treatment at the dose used did not affect the viability or expression of ccR7 by the cells.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, under inflammatory conditions, CCL19 and CCL21 were found to be up-regulated in endothelial cells of the blood-brain barrier (Alt et al, 2002) enabling acute T cell leukemia cells to infiltrate into the central nervous system in a CCR7-dependent manner (Buonamici et al, 2009). Furthermore, CCR7 also contributes to tumor cell survival by activating the PI3K/Akt signaling pathway (Wang et al, 2005).…”
Section: Biological Functionsmentioning
confidence: 99%